PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS, FIXED ASSET RATIO DAN RISIKO PASAR TERHADAP STRUKTUR MODAL - Mochamad Yahdi Khairin; Puji Harto (Diponegoro Journal of Accounting, 2014)
The research aimed to examine the effect of growth opportunity, profitability, fixed assets ratio, and market risk on capital structure. The research uses secondary data sources, data derived from the Indonesian Capital Market Directory (ICMD) and company annual reports contained in BEI. Determined samples used purposive sampling method, which resulted 39 properties and real estate companies, in the period 2010-2012 with a total of 117 observations. Analyzed data used a linear regression analysis, where hypothesis testing is using F test and t-test. Results of the study showed that partially during 2010 to 2012, growth opportunity, profitability and market risk significantly effect with the positive direction of the capital structure, while fixed asset ratio variables have a significant effect with the negative direction of the capital structure.